THE ROLE OF GLUTATHIONE TRANSFERASES IN RENAL CELL CARCINOMA - Ćorić, Vesna M; Plješa-Ercegovac, Marija; Džamić, Zoran (Medicinski podmladak, 2016)
Mounting evidence suggest that members of the subfamily of cytosolic glutathione S-transferases (GSTs) possess roles far beyond the classical glutathione-dependent enzymatic conjugation of electrophilic metabolites and xenobiotics. Namely, monomeric forms of certain GSTs are capable of forming protein: protein interactions with protein kinases and regulate cell apoptotic pathways. Due to this dual functionality of cytosolic GSTs, they might be implicated in both the development and the progression of renal cell carcinoma (RCC). Prominent genetic heterogeneity, resulting from the gene deletions, as well as from SNPs in the coding and non-coding regions of GST genes, might affect GST isoenzyme profiles in renal parenchyma and therefore serve as a valuable indicator for predicting the risk of cancer development. Namely, GSTs are involved in the biotransformation of several compounds recognized as risk factors for RCC. The most potent carcinogen of polycyclic aromatic hydrocarbon diol epoxides, present in cigarette smoke, is of benzo(a)pyrene (BPDE), detoxified by GSTs. So far, the relationship between GST genotype and BPDE-DNA adduct formation, in determining the risk for RCC, has not been evaluated in patients with RCC. Although the association between certain individual and combined GST genotypes and RCC risk has been debated in a the literature, the data on the prognostic value of GST polymorphism in patients with RCC are scarce, probably due to the fact that the molecular mechanism supporting the role of GSTs in RCC progression has not been clarified as yet.